Chance and Design: From Architecture to Institutional Design. Issue 1 (2nd January 2017) - Alexander, Ernest R.
Abstract : Much in Alexander's life happened by chance. Born in Germany, he grew up in South Africa where he discovered design—a continuing concern—and qualified as an architect; chance and inclination led him to practice planning. In Berkeley (CA) for a planning education, curiosity initiated a 30-year academic career as a planning theorist and educator. This Perspective has two threads: design and contingency. Design means devising possible courses of action: Alexander reviews his design engagement at various levels, from designing buildings through policies and plans to institutional design. Contingency planning adapts to complexity and uncertainty; contingency thinking avoids generalizations, hence the need for detailed institutional design. In planning theory, contingency implies dissent and diversity, to suggest that planning is diverse planning practices, each with its planning theories. Alexander's message: Be critical, of theories, institutions, and practices. Be modest: planners' roles in knowledge-centered practices (e.g., spatial planning) should reflect their particular practice. Be confident: planners share their substantive knowledge and apply design and planning skills in the co-construction of knowledge that is participative planning. This is our unique contribution to making a better world.